Peta Konsep Kebekerjaan Lulusan Pendidikan Vokasi - Fitri Nur Mahmudah; Aliyah Rasyid Baswedan (LPPM Politeknik Pratama, 2024)
Vocational education in Indonesia aims to ensure that graduates can have good jobs. This is in accordance with the competencies that have been learned during education or you can also continue to college and develop yourself through entrepreneurial innovation. Entrepreneurship is also an important part of the work of vocational education graduates because this activity results from students' understanding through practical learning with various strategies such as Project-Base Learning or other approaches. Entrepreneurship is a way of learning as a medium for students to develop themselves and improve competencies as needed by the world of work (Mahmudah et al., 2023). Increasing competence through self-development practices. In preparing graduates who are ready to work, vocational schools often encounter problems, namely the large number of students who continue to college compared to students who work. The 1945 Constitution mandates efforts to make the nation's life more intelligent and for the government to strive for and implement a national education system regulated by law, namely Law Number 20 of 2003 concerning the National Education System. One part of the National Education System is vocational education. Vocational High Schools (SMK) as vocational education institutions aim to develop students' abilities to be able to work in certain fields, the ability to adapt to the work environment, see job opportunities and develop themselves in the future (Al Hafidz & Sofyan, 2022).